Implementasi Sistem Informasi Geografis untuk Pelacakan IP Address Daro Domain Menjadi Peta Interaktif - Fachruzi, Faza Reihan; Adek, Rizal Tjut; Aidilof, Hafizh Al Kautsar (Jurnal Ilmiah Global Education, 2025)
This research aims to develop a geographic information system (GIS) capable of tracking the IP address of a domain and visualizing it in the form of an interactive map. In the context of computer networks, IP geolocation is an important aspect in detecting user location for various purposes such as service personalization, network performance improvement through Content Delivery Network (CDN), and compliance with certain regional laws. The system built utilizes the Sequential Search algorithm to facilitate the search for data such as food prices from various markets. The tracking process starts from converting the domain into an IP address, followed by a traceroute to determine the path (hops) through which the data packet travels, and finally mapping the results visually using GIS. The results show that the system is able to identify public, private, and inactive IPs, as well as display data communication routes with marked points on the map. This visualization helps users in analyzing the network, detecting potential disruptions, and making it easier to understand the flow of data traffic. The system is also relevant for use in network monitoring, suspicious activity tracking, and education about internet infrastructure.